THE INFLUENCE OF TRUST IN SUPERIORS ON EMPLOYEES' TRUST IN THE COMPANY WITH JOB EMBEDDEDNESS AS A MODERATING VARIABLE - Mochammad Isa Anshori; Rieneke Ryke Kalalo; Djoko Wijono; Jemadi; Dicki Bagus Chandra (Adisam Publisher, 2026)
This study is a quantitative study with an explanatory approach, namely an approach that uses previous research as the main reference which is then decorated and varied so that it is different from previous research. The data used in this study is quantitative data that researchers obtained from 350 Samsung Smartphone employees spread throughout Indonesia. The data was analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the hypothesis used in this article, namely the variable Trust in Superiors, does not have a positive relationship direction and a significant influence because the P- Values are not below the significance level of 0.05, namely 0.52. This can be caused because not only Trust in Superiors can affect Employee Trust in the company such as Superior Behavior, Work Environment, and other things that can make Employees trust the company. In addition, the Work Engagement variable also cannot moderate the influence of the Trust in Superiors variable on the Employee Trust in the Company variable because the P-Values value is above the significance level of 0.05, namely 0.051. Thus, the first and second hypotheses in the study cannot be proven and accepted.